tv series with multiple parts from the viewers viewpoint: عبد الكريم حسين عباس السوداني (Al-Academy, 2021)
TV drama has gone through many developmental stages until it reached and settled in the form of TV series of thirty episodes. Alongside the development of the TV technologies and the widespread of satellite channels, the form of the TV drama has changed and the series has consisted of two parts and then parts multiplied until they amounted to ten parts and more. This form of TV drama has become an artistic phenomenon, that once the series is displayed on one of the channels and achieves a noticeable success, its producers work to produce a second part of that series and so on. This form of TV drama has remained away from being researched. This has urged the researcher to accomplish this study entitled (TV series of multiple parts from the viewers' viewpoint) which aimed to know the viewers' opinions in many aspects of the TV drama with multiple parts. In the theoretical framework, the researcher studied the development stages of TV drama in the first section and the TV series with multiple parts in the second section. The researcher, in the third chapter, determined the descriptive approach as the questionnaire constitutes one of its main tools. The researcher designed the research tool, which is the questionnaire form that consists of seven questions covering what has been mentioned in the research aims. The research sample is limited to three hundred respondents from Baghdad aged between 15-40 years old